2022
DOI: 10.5194/aab-65-55-2022
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA-0100 positively regulates the differentiation of cashmere goat SHF-SCs into hair follicle lineage via sequestering miR-153-3p to heighten the KLF5 expression

Abstract: Abstract. Circular RNAs (circRNAs) have stable structures, being a covalently closed loop without 5′ and 3′ free ends. They can function as “miRNA sponges” in regulating the expression of their target genes. It was thought that circRNAs are involved in the development of the secondary hair follicle (SHF) in cashmere goats. In our previous investigation, a new circRNA named circRNA-0100 was identified from the SHF of cashmere goats, but its function is unknown. In this work, we found that circRNA-0100 exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Therefore, we speculate that m 6 A-circRNA-ZNF638 may regulate the expression of miR-361-5p in SHF-stem cells. This regulatory mode is highly similar to that reported in investigation on the differentiation of cashmere goat SHF-stem cells into hair follicle lineage, where circRNA-0100 was revealed to directly bind with miR-153-3p, and negatively regulated its expression [15]. Also, in a research on invasion and metastasis of colorectal cancer, Han and colleagues found that circLONP2 bound with miR-17, and negatively regulated its expression [28].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, we speculate that m 6 A-circRNA-ZNF638 may regulate the expression of miR-361-5p in SHF-stem cells. This regulatory mode is highly similar to that reported in investigation on the differentiation of cashmere goat SHF-stem cells into hair follicle lineage, where circRNA-0100 was revealed to directly bind with miR-153-3p, and negatively regulated its expression [15]. Also, in a research on invasion and metastasis of colorectal cancer, Han and colleagues found that circLONP2 bound with miR-17, and negatively regulated its expression [28].…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 81%
“…A r t i c l e miR-361-5p, miR-140-3p, and miR-194 (Fig. 1B), which implies that m 6 A-circRNA-ZNF638 in SHFs of cashmere goats may exert its biological functions through miRNA-mediated pathways as reported in recent publications [13][14][15]. On the other hand, the four m 6 A sites within m 6 A-circRNA-ZNF638 sequence were revealed to have the same motif of GGACU, which is consistent with the m 6 A motif: RRACH (R: A/G; H: A/C/U) reported in linear RNA molecules (Fig.…”
Section: A C C E P T E Dsupporting
confidence: 72%
See 2 more Smart Citations
“…After identifying the differentially expressed circRNAs in each comparison group, combined with the morphological changes of cashmere goat secondary hair follicles in different periods, circRNAs related to the development of secondary hair follicles were screened. In recent years, researchers discovered circRNA1967, circRNA1926, and circRNA-0100 in cashmere goat secondary hair follicles and verified their regulatory roles in secondary hair follicles ( 19 , 22 , 23 ). In this study, 113 circRNAs related to the development of secondary hair follicles, including circRNA5712, circRNA2109, circRNA9127, and circRNA3691, were screened.…”
Section: Discussionmentioning
confidence: 96%